2014
DOI: 10.1007/s00253-013-5467-8
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the peptidoglycan cytoplasmic precursor biosynthetic pathway in cell-free system and rapid screening of antisense oligonucleotides for Mur enzymes

Abstract: Bacterial peptidoglycan is the cell wall component responsible for various biological activities. Its cytoplasmic precursor UDP-N-acetylmuramyl pentapeptide is biosynthesized by the first six enzymes of peptidoglycan synthetic pathways (Mur enzymes), which are all proved to be important targets for antibiotic screening. In our present work, the genes encoding Mur enzymes from Escherichia coli were co-expressed in the cell-free protein synthesis (CFPS) system, and the activities of Mur enzymes derived from CFPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The modulation and detailed analysis of this pathway with enzymes originating from different pathogenic bacteria appears to become feasible (42). We could further extend previous studies with the in vitro expressed Mur enzymes that were only able to reconstitute the reaction catalyzing the formation of the UDP-MurNAc-pentapeptide precursor but lacking the synthesis of the final lipid I and lipid II products by the integral membrane protein MraY and the membrane-associated protein MurG (45). Moreover in comparison to previous approaches (42) we present a fast twostep method for lipid II synthesis, which in addition does not need extensive enzyme preparations and facilitates the engineering of the biosynthetic proteins.…”
Section: Discussionmentioning
confidence: 84%
“…The modulation and detailed analysis of this pathway with enzymes originating from different pathogenic bacteria appears to become feasible (42). We could further extend previous studies with the in vitro expressed Mur enzymes that were only able to reconstitute the reaction catalyzing the formation of the UDP-MurNAc-pentapeptide precursor but lacking the synthesis of the final lipid I and lipid II products by the integral membrane protein MraY and the membrane-associated protein MurG (45). Moreover in comparison to previous approaches (42) we present a fast twostep method for lipid II synthesis, which in addition does not need extensive enzyme preparations and facilitates the engineering of the biosynthetic proteins.…”
Section: Discussionmentioning
confidence: 84%
“…Co-express of yqgR , agm1 , and glmU in CFPS was also performed to reconstitute the UDP-GlcNAc biosynthetic pathway in one pot reaction. The same group further extended the construction of a 6-step biosynthetic pathway leading to the production of UDP-N-acetylmuramyl pentapeptide, a precursor of the bacterial peptidoglycan [ 16 ]. All the metabolic pathway enzymes (murA, murB, murC, murD, murE, and murF) were expressed simultaneously in CFPS, with the final product successfully detected.…”
Section: Cfps Driven Metabolic Engineering (Cfps-me)mentioning
confidence: 99%
“…Different from the in vivo strategies by manipulating the complex transcription and translation machineries, metabolic pathway gene expression levels can be simply controlled by adjusting linear DNA concentrations supplemented to CFPS with coupled transcription-translation reactions under no resource limitation conditions [ 11 ]. Currently, CFPS has been successfully applied to the construction and optimization of metabolic pathways [ [12] , [13] , [14] , [15] , [16] , [17] ] and genetic circuits [ [18] , [19] , [20] , [21] , [22] ]. It has been reported that the CFPS can reduce the time to build metabolic pathways and genetic circuits from days to hours.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of reports have validated this approach. Three- and six-enzyme pathways have recently been generated de novo from DNA inputs in CFS to produce N-acetylglucosamine and a peptidoglycan precursor, respectively [171, 172]. A five-enzyme pathway that transforms tryptophan into a bioactive pigment called violacein has also been demonstrated [49, 56].…”
Section: Platform For Discoverymentioning
confidence: 99%